Effective removal of glyphosate from aqueous systems using synthesized PEG-coated calcium peroxide nanoparticles: kinetics study, H2O2 release performance and degradation pathways - Li, Fan; Choong, Thomas Shean Yaw; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain; Amerhaider Nuar, Nurul Nazihah (Multidisciplinary Digital Publishing Institute, 2023)
Glyphosate (N-phosphonomethyl glycine) is a non-selective, broad-spectrum organophosphate herbicide. Its omnipresent application with large quantity has made glyphosate as a problematic contaminant in water. Therefore, an effective technology is urgently required to remove glyphosate and its metabolites from water. In this study, calcium peroxide nanoparticles (nCPs) were functioned as an oxidant to produce sufficient hydroxyl free radicals (·OH) with the presence of Fe2+ as a catalyst using a Fenton-based system. The nCPs with small particle size (40.88 nm) and high surface area (28.09 m2/g) were successfully synthesized via a co-precipitation method. The synthesized nCPs were characterized using transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), Brunauer–Emmett–Teller analysis (BET), dynamic light scattering (DLS), and field emission scanning electron microscopy (FESEM) techniques. Under the given conditions (pH = 3.0, initial nCPs dosage = 0.2 g, Ca2+/Fe2+ molar ratio = 6, the initial glyphosate concentration = 50 mg/L, RT), 99.60% total phosphorus (TP) removal and 75.10% chemical oxygen demand (COD) removal were achieved within 75 min. The degradation process fitted with the Behnajady–Modirshahla–Ghanbery (BMG) kinetics model. The H2O2 release performance and proposed degradation pathways were also reported. The results demonstrated that calcium peroxide nanoparticles are an efficient oxidant for glyphosate removal from aqueous systems.